G41 A joint collaborative regional network approach to overcome difficulties in diagnosis of paediatric coeliac disease. (12th March 2018) - Hakizimana, A; Heather, N; Pridgeon, J; Ward, N; Afzal, NA
Abstract : Aims: Diagnosis of paediatric coeliac disease (pCD) continues to be a challenge despite the new NICE, BSPGHAN and ESPGHAN guidance. To understand a 'true abnormal serologic result' and the need for a duodenal biopsy, we aimed for a quality improving exercise in a regional network setting. Methods: A two staged quality approach was adopted: An online regional survey was conducted to investigate the currently used serologic screening tests for diagnosis of pCD in the region. Regional paediatricians and pathology laboratories were contacted by phone and email followed by an online survey conducted via the Network Website (AH, NA). A summary presentation of the findings, were presented at the annual regional network meeting followed by a rigorous discussion with active participation of immunologists, paediatric consultants and dieticians from the region. Results: 9/13 hospitals in the regional network participated in the survey. For coeliac screening IgA Anti-tTG is used by all centres (IgA EMA in 7/9 centres (77.8%). 5/9 (55.6%) centres routinely check IgA levels in all cases. 5/9 centres (55.6%) combined IgA and IgG anti-TTG to increase sensitivity. There is a huge variation in the normal range of IgA TTG with the upper normal limit varying from 2.9 to 19. The survey results were presented (AH) at the annual regional network meeting generating an active discussion amongst the attending immunologists, paediatricians, dieticians and specialist nurses, with these conclusions. The huge variation in normal levels, with lack of standardisation in TTG testing, is an issue in the region, as highlighted nationally. The Immunologists highlighted variations even within the same serological test, when using different batches requiring labs to conduct regular quality control checks. A network consensus followed with regards to provision of dietary review for all patients (particularly <10X serologic levels), to ensure adequate gluten intake before consideration of biopsy. Conclusions: pCD is a lifelong condition requiring an accurate diagnosis. The clinicians and immunologists continued to be challenged despite following the correct pathways and guidance. This study highlighting the strengths and benefits of a joint regional collaborative approach to help overcome some of these difficulties.